Outcomes after vascular resection during curative-intent resection for hilar cholangiocarcinoma: a multi-institution study from the US extrahepatic biliary malignancy consortium. Issue 4 (April 2018) - Schimizzi, Gregory V.; Jin, Linda X.; Davidson, Jesse T.; Krasnick, Bradley A.; Ethun, Cecilia G.; Pawlik, Timothy M.; Poultsides, George; Tran, Thuy; Idrees, Kamran; Isom, Chelsea A.; Weber, Sharon M.; Salem, Ahmed; et al.
Abstract: Background: Surgical resection is the cornerstone of curative-intent therapy for patients with hilar cholangiocarcinoma (HC). The role of vascular resection (VR) in the treatment of HC in western centres is not well defined. Methods: Utilizing data from the U.S. Extrahepatic Biliary Malignancy Consortium, patients were grouped into those who underwent resection for HC based on VR status: no VR, portal vein resection (PVR), or hepatic artery resection (HAR). Perioperative and long-term survival outcomes were analyzed. Results: Between 1998 and 2015, 201 patients underwent resection for HC, of which 31 (15%) underwent VR: 19 patients (9%) underwent PVR alone and 12 patients (6%) underwent HAR either with (n = 2) or without PVR (n = 10). Patients selected for VR tended to be younger with higher stage disease. Rates of postoperative complications and 30-day mortality were similar when stratified by vascular resection status. On multivariate analysis, receipt of PVR or HAR did not significantly affect OS or RFS. Conclusion: In a modern, multi-institutional cohort of patients undergoing curative-intent resection for HC, VR appears to be a safe procedure in a highly selected subset, although long-term survival outcomes appear equivalent. VR should be considered only in select patients based on tumor and patient characteristics.